Water resources management in Zambia: a case of cumulative impacts associated with copper mining in the Upper Kafue Catchment, Copperbelt Province, Zambia - Mwamba, Bright (Department of Chemical Engineering, 2021)
Water resources management is high on the agenda both locally and globally because of its important role in social, economic and environmental development. For example, as part of the 2030 Agenda for Sustainable Development, all United Nations Member States adopted 17 Sustainable Development Goals (SDGs) in 2015 that covered thematic issues including water, energy, climate, oceans, urbanization, transport, science and technology. Sustainable Development Goal (SDG) no.6, which targets universal access to safe and affordable drinking water for all by 2030, is of particular interest in this study. The mining industry contributes to socio-economic development; however, it has also contributed to declining water quality in rivers and lakes in many regions globally. In this study, the status and governance of water resources within the Copperbelt province of Zambia over the period 2000 to 2020 was examined. The study investigated population and economic growth within the region and its correlation with changes in water quality and quantity. The research also focused on understanding the ways copper mining is affecting local water resources. The study also investigated challenges faced by regulators and institutions in the water sector, and considered how these challenges could be addressed. Secondary data was obtained from government institutions within Zambia such as National Water Supply and Sanitation Council (NWASCO), Water Resources Management Authority (WARMA) and Zambia Environmental Management Agency (ZEMA), which are the key institutions in the water sector and the environment. Semi-structured interviews were also conducted with the three key institutions in the water and pollution control sectors. The results showed that the total population in the Copperbelt province has increased by 20% since 2000 to a total of 1 972 317 in 2010. The population is projected to be 2 669 635 in 2020, representing about 27% increase from 2010. The rural population is projected to be 423 511 in 2020, representing about 11% increase from 2010 while the urban population will be 2 246 124 in 2020 representing about 29% increase from 2010. The majority of this growth has occurred in urban areas, which grew by about 30% from 2000 to a total of 1 595 456 in 2010. Rural population has increased by 8% since 2000 to a total of 376 861. The results also showed increased economic activities driven mainly by copper mining. Water abstraction has generally declined since 2000 mainly due to decrease in mining activities. In 2000, about 1 million m3 /day was abstracted in the Copperbelt province and about 600 000 m3 per day in 2005. The reduction in 2005 could be attributed to reduction in mining activities and institutional changes in the water sector. Water production and consumption from commercial utilities has generally been in decline from 2000 to 2017. This is also the case with water consumption per capita and water production per capita. For example, water consumption per capita per day in 2001 was 203 liters and reduced to 113 liters in 2017, representing a 44% reduction in consumption. The results showed that water consumption from 2004 to 2008 averaged 100 million m3 while the production averaged 160 million m3 per year. NWASCO attributed the general downward trend in water production and consumption in the province to maintenance and rehabilitation of water infrastructure, and investment in new infrastructure, thereby reducing the unaccounted-for water. The other reason could be that new housing developments prefer to use groundwater sources rather than utility water (supplied by water companies). The reduction could also be attributed to the cost of water and that consumers needed to adjust from the background where utility services such as water supply and sanitation were the sole responsibilities of the mines (ZCCM), prior to privatization. In terms of water supply and sanitation coverage, there has been an increased coverage since 2000. In 2001, the population that had access to water supply and sanitation was 81% and 46%, respectively. Therefore, roughly 50% of the population had no access to sanitation. However, in 2017 the population with access to water supply and sanitation was 91% and 75%, respectively. This represented only 25% of the population in serviced areas that had no access to sanitation. Between 2007 and 2008, the sanitation coverage had seen a reduction compared to the year 2006. This was due to institutional changes on the Copperbelt province, and the 2008 economic recession – the mine townships that were previously serviced by an asset holding after privatization of the mines were taken over by other utility companies. Consequently, the service delivery in the province initially dropped, but then started increasing again in 2009.